The impact of demographic factors on the level of knowledge about primary and secondary prevention of cervical cancer among patients in Lublin voivodeship - Puzio, Anna; Kułak, Krzysztof; Repa, Małgorzata; Ruszczyk, Joanna; Skórzyńska-Dziduszko, Katarzyna (Family Medicine & Primary Care Review, 2016)
Background. Cervical cancer (CC) is among the most-commonly detected cancers affecting women worldwide. The primary means of preventing CC is the Human Papillomavirus (HPV) vaccine. Moreover, CC can be detected early by a screening test, which is available free of charge in Poland for women in the 25–59 year-old age group (i.e., those at the greatest risk of CC). Objectives. To assess the level of knowledge among patients in Lublin voivodeship, Poland, concerning both the primary and secondary prevention of CC; to analyze the impact of demographic factors on participation in CC screening. Material and methods. The study was carried out on a group of patients (n = 230), who filled out a questionnaire including questions on the primary and secondary prevention of CC. Participation was voluntary and anonymous. The data was analyzed using Statistica 10.0 software (StatSoft, USA ). Results . It was shown that subjects from small towns and rural areas formed the largest group of women who indicated that they had fewer than one gynecological visit per year. 40% (n = 28) of the inhabitants of rural areas, 29% (n = 9) of the inhabitants of small towns and 70% (n = 57) of the inhabitants of cities reported that they had had a cytological test at least once in their life. 25% (n = 57) of all respondents had been vaccinated against HPV. Among rural inhabitants, 83% (n = 58) reported that they had not received a HPV vaccination. Conclusions . Currently, the priority is to focus on prevention campaigns in rural areas and small towns, where the level of knowledge about the risk of CC is much lower than in larger cities.